Soundpeaking – Hydropeaking induced changes in river soundscapes. (28th November 2017) - Lumsdon, A.E.; Artamonov, I.; Bruno, M.C.; Righetti, M.; Tockner, K.; Tonolla, D.; Zarfl, C.
Abstract: Underwater soundscapes and their unique acoustic signatures are mainly generated through movement of streambed sediment, subsequent particle collisions, and turbulence created by water flowing over submerged obstructions such as rocks and woody debris. This study characterized river soundscapes in Alpine rivers of Trentino, (North East Italy) with the combined use of hydrophones and a new microelectricalmechanical systems based device (Hydroflown) that is capable of measuring particle velocity components of the sound field. Pool and riffle habitats affected and unaffected by hydropeaking were characterized in terms of their particle velocity and sound pressure levels across 10 octave bands (acoustic signature) to assess temporal variations in overall sound levels, changes in frequency composition, and relationship to hydromorphological habitat parameters. Data revealed that soundscapes affected by hydropeaking are highly homogenized, and sound pressure levels are strongly correlated with turbine discharge, which results in rapid, multiple‐fold spikes in low frequency amplitude levels within the typical hearing range of common teleost fish species. The outcomes of this study provide the basis for further examination of the resulting behavioural and physiological responses of organisms to anthropogenic changes in river soundscapes.